2023
DOI: 10.1126/sciadv.adh0135
|View full text |Cite
|
Sign up to set email alerts
|

Programmed fluorine binding engineering in anion-pillared metal-organic framework for record trace acetylene capture from ethylene

Abstract: Porous physisorbents are attractive candidates for selective capture of trace gas or volatile compounds due to their low energy footprints. However, many physisorbents suffer from insufficient sorbate-sorbent interactions, resulting in low uptake or inadequate selectivity when gases are present at trace levels. Here, we report a strategy of programmed fluorine binding engineering in anion-pillared metal-organic frameworks to maximize C 2 H 2 binding affinity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…However, low working capacity and dissatisfactory selectivity make them not the best choice for physical sorption separation . Metal–organic frameworks (MOFs) have shown great potential in gas adsorption and separation due to their high surface area, modified pores, adjusted topological structure, and high adsorption capacity, as compared to traditional porous materials like zeolites and activated carbon. Several classic MOFs, including ZU-801, DUT-52, ZJU, , and DMOF, have exhibited excellent gas storage and separation performance. Researchers have made efforts to enhance gas adsorption and separation properties by functionalizing MOFs through the introduction of functional groups (−CH 3 , −NH 2 , −OH), tuning of pore size and the construction of open metal sites (OMSs). Previous studies have shown that providing an appropriate aromatic pore environment can enhance interactions between light hydrocarbon molecules and the MOF framework through dispersion and induction forces, a widely used and effective approach. , Our research group is committing to the engineering of pores to achieve efficient gas capture. ,,, In our work, we aim to introduce additional functional sites into the aromatic pore environment to achieve a synergistic effect from multiple adsorption sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, low working capacity and dissatisfactory selectivity make them not the best choice for physical sorption separation . Metal–organic frameworks (MOFs) have shown great potential in gas adsorption and separation due to their high surface area, modified pores, adjusted topological structure, and high adsorption capacity, as compared to traditional porous materials like zeolites and activated carbon. Several classic MOFs, including ZU-801, DUT-52, ZJU, , and DMOF, have exhibited excellent gas storage and separation performance. Researchers have made efforts to enhance gas adsorption and separation properties by functionalizing MOFs through the introduction of functional groups (−CH 3 , −NH 2 , −OH), tuning of pore size and the construction of open metal sites (OMSs). Previous studies have shown that providing an appropriate aromatic pore environment can enhance interactions between light hydrocarbon molecules and the MOF framework through dispersion and induction forces, a widely used and effective approach. , Our research group is committing to the engineering of pores to achieve efficient gas capture. ,,, In our work, we aim to introduce additional functional sites into the aromatic pore environment to achieve a synergistic effect from multiple adsorption sites.…”
Section: Introductionmentioning
confidence: 99%
“…2–17 In addition, the structure of MOFs is long-range ordered, which enables the structure–activity relationships of MOFs easy to be revealed by single crystal X-ray diffraction (SCXRD). 18–21 In this context, MOFs have been widely used in various fields, such as gas adsorption and separation, 22–37 pollutant capture, 38–40 electrical/ionic conduction, 41–43 selective recognition, 44–46 and heterogeneous catalysis. 47–50 At the initial stage, scientists mainly focused on the synthesis of MOFs with novel structures and the exploration of new functions of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging class of porous solid materials, metal–organic frameworks (MOFs) with high porosity, adjustable pore size/shape, and modifiable pore environment have demonstrated great advantages in gas separation, compared with traditional adsorbents including zeolite, activated carbon, silica gel, etc. Enormous endeavors are committed to developing suitable MOFs for C 2 H 2 /CO 2 separation, and several important progresses have been made in the adjustment strategy for C 2 H 2 -selective adsorption behavior, including but not limited to open metal sites regulation, ligand functional modification, inorganic anion introduction, pore space partition, and C 2 H 2 nanotrap construction. The preference of MOFs for C 2 H 2 is due to the strong host–guest interaction between C 2 H 2 and the framework, such as hydrogen bonding, Lewis acid–base interactions, and π-complexation. UiO-66 is a classic Zirconium MOF assembled from a Zr 6 O 4 (OH) 4 (CO 2 ) 12 cluster and 1,4-benzenedicarboxylic acid (H 2 BDC), containing two types of cages, viz. super octahedron and super tetrahedron .…”
Section: Introductionmentioning
confidence: 99%